Scrub typhus at the local hyper-endemic area, central Vietnam: epidemiology, clinical presentations, and laboratory features at admission - Tran, Hanh Thi Duc; Le, Anh Kim (International Journal Of Community Medicine And Public Health, 2026)
Background: The objective of this study was to deacribe the epidemiological characteristics, clinical and laboratory features at admission of scrub typhus at a local hyper-endemic area-Khanh Hoa province, central Vietnam. Methods: From August 2018 to March 2020, a hospital-based active surveillance was applied to collect suspected adult scrub typhus cases from 9 public/district hospitals. A community survey was conducted to investigate epidemiological factors. PCR and ELISA IgM tests were applied to confirm cases. Using standardized questionnaires, trained health staffs gathered demographic, clinical and laboratory data, and assessed patients’ household conditions, personal behaviours/protective equipment, and vector exposure. Data was recorded using Open data kit (ODK) on Android devices and analysed with STATA version 15. Results: Thirty-two confirmed cases were identified and analysed, with males accounting for 56.3%. Of these, 56.2% were farmers or worked in forests/mountain fields/garden. About 60% engaged in risky behaviours (urinating in the forest/near bushes/field; passing riverside; resting directly on household floor). About 96.9% lived in poor sanitation households and 60% always saw mice around their homes. Despite 72% worked in hazardous environment, only 34.4% used personal protective equipment. Common clinical symptoms beside fever included headache (84.4%), fatigue (75.0%), myalgia (68.8%), heart rate>90/min (50.0%), lymphadenopathy (34.4%). An eschar was found in 59.4%. Abnormal laboratory findings included neutrophils>70% (53.3%), lymphocytes<20% (65.6%), a neutrophils/lymphocytes ratio (<1 or >2) (60.0%), platelet<150,000/ml (56.3%), and AST/AL ≥40U/l (86.7%). Conclusions: Comprehensive consideration of epidemiological features, clinical and laboratory examination is crucial for diagnosing scrub typhus upon admission. Clinicians in endemic areas need enhance their understanding of local scrub typhus.